Exploring Sweden and South Africa’s Responses to Mass Migration during the Period 2015–2019 - Pragna Rugunanan; Celine Meyers (The Thinker)
Sweden and South Africa are two major transnational destinations and attract large numbers of refugees and migrants, primarily due to their ease of immigration policies. Besides their unique historical relations which can be traced back to as early as the 1890s, both countries continue to experience high volumes of mass migration and forced mobility which peaked in 2015. Following the so-called ‘Syrian refugee crisis’, Sweden witnessed the second largest asylum applications in Europe. At around the same time, South Africa experienced its highest backlog of asylum applications. It is against this backdrop of a long and diverse history of relations and ongoing migration that we seek to engage with the responses of both countries to mass migration using a comparative approach. The article presents a historical perspective of migration between Sweden and South Africa and examines their ongoing migration policy debates. It concludes with an analysis of current political contestations and some key lessons for each country.